Advances in Neural Signal Processing 2020
DOI: 10.5772/intechopen.88337
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Spectral Perturbation during Upper Limb Diagonal Movements

Abstract: While it has been suggested that diagonal rhythmical bilateral movements promote improvement in motor and cognitive functions, no study that we are aware of has actually examined electrophysiological changes during diagonal movements. Therefore, we aimed to study cerebral activity during the performance of diagonal and vertical movements (DM and VM, respectively), through EEG recording focusing on theta, alpha, and beta frequency bands. Following independent component analysis, we computed time-frequency and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…especially the visual system [159,160]. Similar to Rimbert et al [5], Marson et al [161] further found post-movement beta rebound [162] between consecutive trials, namely, increased beta activity both in diagonal and vertical movements.…”
Section: Diagonal Movementmentioning
confidence: 69%
See 2 more Smart Citations
“…especially the visual system [159,160]. Similar to Rimbert et al [5], Marson et al [161] further found post-movement beta rebound [162] between consecutive trials, namely, increased beta activity both in diagonal and vertical movements.…”
Section: Diagonal Movementmentioning
confidence: 69%
“…Only a few recent studies have examined electrophysiological changes during diagonal movements. A rare pioneering study [161] has found increased frontal theta activity during the initiation of diagonal movement, compared to purely vertical movements, which were also studied. The increased frontal theta was possibly due to greater computational effort [86,95,140].…”
Section: Diagonal Movementmentioning
confidence: 99%
See 1 more Smart Citation